2004
DOI: 10.1002/biof.5520200306
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels and redox status of coenzyme Q10 in infants and children

Abstract: This is the first study concerning age-related values of plasma level and redox status of CoQ10 in apparently healthy children. Decreased CoQ10 values could be involved in various pathological conditions affecting childhood. Therefore, the application of age-adjusted reference values may provide more specific criteria to define threshold values for CoQ10 deficiency in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…In both, the patient and the control groups, a negative correlation between the age of the children and the CoQ 10 plasma concentration was found, thus, confirming previous findings (21) that preschoolers have increased CoQ 10 levels in comparison to school‐aged children. While the age ranges in both groups are comparable, the mean age in the patient group shifts in favour of elder children.…”
Section: Discussionsupporting
confidence: 88%
“…In both, the patient and the control groups, a negative correlation between the age of the children and the CoQ 10 plasma concentration was found, thus, confirming previous findings (21) that preschoolers have increased CoQ 10 levels in comparison to school‐aged children. While the age ranges in both groups are comparable, the mean age in the patient group shifts in favour of elder children.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the portion of UN10 relative to TQ10 (UN10/TQ10 ratio) in cord plasma appeared to decrease with age (except in cases of asphyxia, Table III). The median UN10/TQ10 ratio in our cord plasma samples was 24%, similar to that reported in venous cord plasma (26%) and peripheral plasma of neonates 1 – 5 days old (25 – 31%) [50] compared to UN10/TQ10 ratios in the peripheral plasma of infants 1– to 12 months old (9 – 19%), children and adolescents 0– to 17 years old (3 – 4%), and non-pregnant women 26– to 55 years old (9%) (Table III) [45,51]. …”
Section: Resultsmentioning
confidence: 73%
“…The current results are in line with those of Miles et al (32), who found that the redox statuses and total plasma CoQ10 concentrations were similar in younger (0.2-7.6 y) and older children (10.4-17.4 y), though younger children had higher mean lipid-adjusted total CoQ10 concentrations. Likewise, we previously showed a distinct age-dependent decrease in lipid-adjusted CoQ10 plasma concentrations in infants and children (33). Infants in the first to the fourth months of life had higher oxidized proportions of CoQ10 (median 19 vs. 9% in older infants in the first year of life).…”
Section: Discussionmentioning
confidence: 88%